PENGARUH KARAKTERISTIK PEKERJAAN DAN KEPUASAN KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIOR (STUDI KASUS PADA PERAWAT RS PEKANBARU MEDICAL CENTER) - Alwi, Widya Wardhani; ", Kasmiruddin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2019)
This research supposed to know the the influence of work characteristics and job satisfaction on organizational citizenship behavior. This study used a questionnaire as a data collection tool that was distributed to 77 respondents at nurse in the hospital Pekanbaru Medical Center. And then, the data is processed with descriptive analysis and statistical analysis using SPSS 22.0 by conducting validity, reliability testing, simple linear regression analysis, multiple linear analysis, determination analysis (R2) and hypothesis testing with t test (partial test) and F test (simultaneous test).The results showed that the first hypothesis testing, Job Characteristics of Organizational Citizenship Behavior is t arithmetic (5.952) > t table (1.992), meaning Job Characteristics significantly influence Organizational Citizenship Behavior. Second Job Satisfaction of Organizational Citizenship Behavior is t count (5,788) > t table (1,992), meaning that Job Satisfaction has a significant effect on Organizational Citizenship Behavior. Test results F arithmetic (35,421) > F table (3.12), meaning that the Work Characteristics and Job Satisfaction simultaneously have a significant effect on Organizational Citizenship Behavior.  Keywords: work characteristics,  job satisfaction, organizational citizenship behavior.